2012
DOI: 10.1152/ajpgi.00327.2011
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal lavender modulates the enteric microbiota to protect against Citrobacter rodentium-induced colitis

Abstract: Inflammatory bowel disease, inclusive of Crohn's disease and ulcerative colitis, consists of immunologically mediated disorders involving the microbiota in the gastrointestinal tract. Lavender oil is a traditional medicine used to relieve many gastrointestinal disorders. The goal of this study was to examine the therapeutic effects of the essential oil obtained from a novel lavender cultivar, Lavandula × intermedia cultivar Okanagan lavender (OLEO), in a mouse model of acute colitis caused by Citrobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 70 publications
0
24
1
Order By: Relevance
“…Its biochemical composition is the key to understand the bioactivities of L. £ intermedia EOs such as antibacterial, antifungal, antiparasitic, insecticide, antioxidant and anti-inflammatory agents (Papachristos et al 2004;Torras-Claveria et al 2007;Jianu et al 2013). These properties support the potential use of L. £ intermedia EOs as natural cosmetics and natural pharmaceutical ingredients useful for relieving gastrointestinal disorders and for fighting human protozoal pathogens (Moon et al 2006;Baker et al 2012). …”
Section: Inhibitory Activity On Loxmentioning
confidence: 60%
“…Its biochemical composition is the key to understand the bioactivities of L. £ intermedia EOs such as antibacterial, antifungal, antiparasitic, insecticide, antioxidant and anti-inflammatory agents (Papachristos et al 2004;Torras-Claveria et al 2007;Jianu et al 2013). These properties support the potential use of L. £ intermedia EOs as natural cosmetics and natural pharmaceutical ingredients useful for relieving gastrointestinal disorders and for fighting human protozoal pathogens (Moon et al 2006;Baker et al 2012). …”
Section: Inhibitory Activity On Loxmentioning
confidence: 60%
“…The discrepancy between studies suggests that components within the diet alter the intestinal microbiota composition. Indeed, investigators showed that diets fortified with lavender extract decreased the abundance of Proteobacteria in mice infected with C. rodentium [77], an observation linked to the exclusion of Proteobacteria by bacteria within the Firmicutes phylum [78]. A number of butyrogenic bacteria (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis has been observed in IBD patients, and the microbiota has been shown to induce or even prevent colitic disease in mouse models [2], [3]. We recently demonstrated that the intestinal microbiota protects against lethal infectious colitis by regulating protective inflammatory responses [2] and plays a major role in modulating pharmacological efficacy of drugs to attenuate colitis [4]. However, little is known about the effects of dietary lipids on inducing specific microbial changes that are either protective or detrimental in IBD.…”
Section: Introductionmentioning
confidence: 99%